Psychological distress, role, and identity changes in mothers following a diagnosis of cancer: A systematic review. Issue 12 (19th October 2018) - Kuswanto, Carissa Nadia; Stafford, Lesley; Sharp, Jessica; Schofield, Penelope
Abstract: Objective: To systematically review findings of the impact of cancer diagnosis and treatment on mothers' psychological well‐being, roles, and identity and to explore the psychosocial factors that contribute to mothers' psychological well‐being. Methods: Six databases were searched for research articles and theses exploring the association between the impact of cancer diagnosis and treatment on mothers' psychological well‐being, identity, and role, and the psychosocial factors contributing to mothers' psychological distress regardless of their cancer type and stage. The Mixed‐Method Appraisal Bias Tool was used to assess the selected studies' methodological quality. Results: A total of 30 qualitative, quantitative, and mixed‐method studies were deemed eligible for inclusion. Most studies reported that mothers experienced significant psychological distress, changes to or loss of parenting efficacy, maternal identity, and role. Psychosocial factors that contributed to mothers' distress included mothers' young age, presence of metastases, lower parenting efficacy, fear of cancer recurrence, higher illness intrusiveness, and lack of appropriate support. Four main themes emerged from the qualitative studies: psychological impact of cancer on mothers, changes in maternal identity and role, relationship changes and concerns for their children, and meaning‐making in cancer experience. Conclusions: Changes in mothers' psychological well‐being, role, and identity occurred across cancer diagnoses, treatment, and recovery trajectories. The evidence suggests that mothers may benefit from continued and tailored psychosocial support to cope with these challenges, even after treatment is completed. Further studies with improved methodological quality are needed to explore these issues in depth.